2013
DOI: 10.1097/01.ogx.0000429295.65513.69
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype Versus Microarray Testing for Genetic Abnormalities After Stillbirth

Abstract: Background-Genetic abnormalities have been associated with 6 to 13% of stillbirths, but the true prevalence may be higher. Unlike karyotype analysis, microarray analysis does not require live cells, and it detects small deletions and duplications called copy-number variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…In recent years, chromosomal microarray analysis has emerged as a major diagnostic tool for evaluation of congenital anomalies or neuropsychiatric disorders (7,8,25). Our data further support the utility of this technology for diagnosis of pediatric CKD.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In recent years, chromosomal microarray analysis has emerged as a major diagnostic tool for evaluation of congenital anomalies or neuropsychiatric disorders (7,8,25). Our data further support the utility of this technology for diagnosis of pediatric CKD.…”
Section: Discussionsupporting
confidence: 67%
“…Each one of the 131 known genomic disorders had frequencies of 1% or less in controls. The criteria for likely pathogenic and reportable CNVs were adapted from prior recommendations for interpretation of microarray data (7,8,25,29): (a) CNV size of 500 kb or greater, with frequency of 0.02% or less in controls and absence in the CHOP cohort (since this represents a reference healthy pediatric population; ref. 30) and (b) partial overlap with a known genomic disorder or overlap with likely pathogenic CNVs reported in the International Standards for Cytogenomic Arrays (ISCA) database (http://www.ncbi.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 In this issue of the Journal, Reddy and colleagues demonstrate the incremental value of chromosomal microarray in the analysis of stillborn pregnancies. 8 As compared with karyotyping, microarray analysis had a higher likelihood of obtaining a result and identified an increased incidence of genomic abnormalities among stillborn infants.…”
mentioning
confidence: 99%
“…The latter issue is being addressed by the establishment of large databases of both healthy and affected individuals, with post-natal follow-up (indeed, databases derived from post-natal populations cannot be extrapolated to fetal populations). Currently, microarrays are recommended in the presence of: 1) fetuses with structural anomalies and normal karyotype (approximately 5%-10% of them will be found to have microdeletions or microduplications of clinical significance); in stillbirth: a large study has found that use of CGH compared with traditional karyotyping significantly increases the yield (87% vs 70%, p<0.01) and the detection of aneuploidy or pathogenic genomic imbalances (8% vs 6%, p<0.01), independently from the presence of anomalies [14]. It is expected that microarrays will soon replace traditional karyotyping (few karyotyped cells per sample will still be required in addition to CGH to detect triploidies and balanced translocations).…”
Section: Prenatal Diagnosis In the Age Of Genomicsmentioning
confidence: 99%